Prevalence of Salmonella in fresh produce tomatoes sold in open market in Ouagadougou, Burkina Faso - Bognini, H.; Kagambèga, A.; Tiendrebeogo, W.P.B.; Sawadogo, A.; Barro, N.; Knight-Jones, Theodore J.D.; Dione, Michel M. (Scientific Research Publishing, Inc., 2023)
Tomato is a widely consumed vegetable in Burkina Faso and throughout the world. However, when handled improperly, it can serve as a vector of pathogen transmission to human if ingested raw or through cross-contamination with cooked food. This study aimed to determine the prevalence of Salmonella spp. from tomatoes sold in the markets of Ouagadougou, Burkina Faso and characteristics of vending conditions. One hundred and ninety-eight (198) different tomato samples were randomly purchased from one hundred and thirteen (113) different vendors in the markets of Ouagadougou. The samples were examined and classified into three categories according to their texture and the level of deterioration. The prevalence of Salmonella spp. identification was determined using standard microbiological methods. A survey was conducted using a questionnaire on transport and vending conditions for tomatoes. In total, Salmonella prevalence was 19.19% in all tomato’s samples analyzed and was 18.18% for intact category, 22.73% in D2 category and 16.67% in category D4. The survey revealed poor transport and sales conditions for the majority of tomato sellers. The present study revealed the presence of Salmonella in tomatoes samples. These results highlight the risk associated with the consumption of tomatoes if hygienic practices are not respected during tomatoes handling and preparation. The results of the study also show the need to wash tomatoes systematically after purchase with a disinfectant, especially tomatoes sold in open markets in developing countries.